In utero Therapy for the Treatment of Sickle Cell Disease: Taking Advantage of the Fetal Immune System - Cortabarria, Alba Saenz de Villaverde; Makhoul, Laura; Strouboulis, John; Lombardi, Giovanna; Oteng-Ntim, Eugene; Shangaris, Panicos (Frontiers in Cell and Developmental Biology, 2021)
Sickle Cell Disease (SCD) is an autosomal recessive disorder resulting from a β-globin gene missense mutation and is among the most prevalent severe monogenic disorders worldwide. Haematopoietic stem cell transplantation remains the only curative option for the disease, as most management options focus solely on symptom control. Progress in prenatal diagnosis and fetal therapeutic intervention raises the possibility of in utero treatment. SCD can be diagnosed prenatally in high-risk patients using chorionic villus sampling. Among the possible prenatal treatments, in utero stem cell transplantation (IUSCT) shows the most promise. IUSCT is a nonmyeloablative, non-immunosuppressive alternative conferring various unique advantages and may also offer safer postnatal management. Fetal immunologic immaturity could allow engraftment of allogeneic cells before fetal immune system maturation, donor-specific tolerance and lifelong chimerism. In this review, we will discuss SCD, screening and current treatments. We will present the therapeutic rationale for IUSCT, examine the early experimental work and initial human experience, as well as consider primary barriers of clinically implementing IUSCT and the promising approaches to address them.